Effect of Nitrogen Addition on Soil Microbial Functional Gene Abundance and Community Diversity in Permafrost Peatland - Xiuyan Ma; Yanyu Song; Changchun Song; Xianwei Wang; Nannan Wang; Siqi Gao; Xiaofeng Cheng; Zhendi Liu; Jinli Gao; Yu Du (Microorganisms, 2021)
Nitrogen is the limiting nutrient for plant growth in peatland ecosystems. Nitrogen addition significantly affects the plant biomass, diversity and community structure in peatlands. However, the response of belowground microbe to nitrogen addition in peatland ecosystems remains largely unknown. In this study, we performed long-term nitrogen addition experiments in a permafrost peatland in the northwest slope of the Great Xing’an Mountains. The four nitrogen addition treatments applied in this study were 0 g N·m−2·year−1 (CK), 6 g N·m−2·year−1 (N1), 12 g N·m−2·year−1 (N2), and 24 g N·m−2·year−1 (N3). Effects of nitrogen addition over a period of nine growing seasons on the soil microbial abundance and community diversity in permafrost peatland were analyzed. The results showed that the abundances of soil bacteria, fungi, archaea, nitrogen-cycling genes (nifH and b-amoA), and mcrA increased in N1, N2, and N3 treatments compared to CK. This indicated that nitrogen addition promoted microbial decomposition of soil organic matter, nitrogen fixation, ammonia oxidation, nitrification, and methane production. Moreover, nitrogen addition altered the microbial community composition. At the phylum level, the relative abundance of Proteobacteria increased significantly in the N2 treatment. However, the relative abundances of Actinobacteria and Verrucifera in the N2 treatment and Patescibacteria in the N1 treatment decreased significantly. The heatmap showed that the dominant order composition of soil bacteria in N1, N2, and N3 treatments and the CK treatment were different, and the dominant order composition of soil fungi in CK and N3 treatments were different. The N1 treatment showed a significant increase in the Ace and Chao indices of bacteria and Simpson index of fungi. The outcomes of this study suggest that nitrogen addition altered the soil microbial abundance, community structure, and diversity, affecting the soil microbial carbon and nitrogen cycling in permafrost peatland. The results are helpful to understand the ...